MicroRNA-Dependent Control of Sensory Neuron Function Regulates Posture Behavior in Drosophila. - Klann, M.; Issa, A.R.; Pinho, S.; Alonso, C.R. (Journal of Neuroscience, 2021)
All what we see, touch, hear, taste, or smell must first be detected by the sensory elements of our nervous system. Sensory neurons, therefore, represent a critical component in all neural circuits and their correct function is essential for the generation of behavior and adaptation to the environment. Here, we report that the evolutionarily-conserved microRNA (miRNA) miR-263b plays a key behavioral role in Drosophila melanogaster through effects on the function of larval sensory neurons. Several independent experiments (in 50:50 male:female populations) support this finding: first, miRNA expression analysis, via reporter expression and fluorescent-activated cell sorting (FACS)-quantitative PCR (qPCR) analysis, demonstrate miR-263b expression in larval sensory neurons. Second, behavioral tests in miR-263b null mutants show defects in self-righting, an innate and evolutionarily conserved posture-control behavior that allows larvae to rectify their position if turned upside-down. Third, competitive inhibition of miR-263b in sensory neurons using a miR-263b "sponge" leads to self-righting defects. Fourth, systematic analysis of sensory neurons in miR-263b mutants shows no detectable morphologic defects in their stereotypic pattern, while genetically-encoded calcium sensors expressed in the sensory domain reveal a reduction in neural activity in miR-263b mutants. Fifth, miR-263b null mutants show reduced "touch-response" behavior and a compromised response to sound, both characteristic of larval sensory deficits. Furthermore, bioinformatic miRNA target analysis, gene expression assays, and behavioral phenocopy experiments suggest that miR-263b might exert its effects, at least in part, through repression of the basic helix-loop-helix (bHLH) transcription factor Atonal Altogether, our study suggests a model in which miRNA-dependent control of transcription factor expression affects sensory function and behavior.SIGNIFICANCE STATEMENT Sensory neurons are key to neural circuit function, but how these neurons acquire their specific properties is not well understood. Here, we examine this problem, focusing on the roles played by microRNAs (miRNAs). Using Drosophila, we demonstrate that the evolutionarily-conserved miRNA miR-263b controls sensory neuron function allowing the animal to perform an adaptive, elaborate three-dimensional movement. Our work thus shows that microRNAs can control complex motor behaviors by modulating sensory neuron physiology, and suggests that similar miRNA-dependent mechanisms may operate in other species. The work contributes to advance the understanding of the molecular basis of behavior and the biological roles of microRNAs within the nervous system.